Samples of the phenomenon of innovation in Nigerian Arabic political poetry - Masama, Abubakar Adamu; Sabi'u Auwal, Abdulwahid (Journal of Humanities & Social Sciences, 2021)
Nigerian political poetry is currently witnessing a remarkable renewal. Indeed, The political situation in Nigeria has produced brilliant poets who have taken political poetry as one of their most important weapons for them to defend their political and tribal views, this type of poetry has acquired different innovation, this research represents a study of the phenomenon of renewal in Nigerian Arabic poetry, this research comes from the point of view of the researchers' observation that this innovative phenomenon of Nigerian political poetry still lacks what it deserves to be studied. The most important findings of this research are: the current political conditions in Nigeria have imposed a significant renewal in Nigerian political poetry, hence the need for further research in the field.
Keywords: trends; renewal; poetry; politics; Nigeria